Water Projects Related Involuntary Displacement in Nepal - Bisangkhe, Shiva (Water Nepal, 2004)
Development interventions can result in involuntary displacement of families and communities, as can natural calamities like earthquake, flood, and landslides as well as wars and internal strife. In all instances forced departures from home and livelihood is directly or indirectly attributable to the action of the state (Bhattarai, 2001). Since development projects conceived and implemented by the state are considered as nation building, the state often ignores the hardship experienced by the displaced. Because the extraneous forces, which induce involuntary displacement, are often alien to local communities the experience can cause socio-economic stress that transcends the immediate and can even be inter-generational. The displaced are usually poor, marginalised, uneducated, and unorganised, and the price they pay is heavy. Women, children and other vulnerable groups suffer the most. Displaced persons also face the risk of impoverishment, which comprises landlessness, joblessness, homelessness, marginalisation, poor health, food insecurity, loss of common property resources, and unravelling of the social fabric. This paper reviews the literature on involuntary displacement related to water projects in Nepal and looks at relevant legal provisions and the policies of financing agencies. The purpose of the paper is to raise questions about the adequacy of Nepal’s legal and policy framework to handle the social and economic rehabilitation of families displaced by water projects. Water Nepal Vol.11(1) 2004 pp.85-103